Non-Information of Side Effects and Precautions of Drugs: Deficiency in Service - Yadav, Mukesh; Rastogi , Pooja (Journal of Indian Academy of Forensic Medicine, 2014)
Non information of important side effects of drugs may amount to deficiency in service on the part of the doctor. It is a case in which a doctor prescribed an antidiabetic drug to a patient who was alcoholic and diabetic without proper diagnosis and side effects of hypoglycaemia was not informed and precautions of antidiabetic drug that it should be taken before food was also not informed. In a case before District Forum no negligence was found, but in appeal SCDRC reveres the order of District Forum and pronounced well reasoned judgment and ordered for compensation for non discharge of duty by the doctor and declared it as deficiency in Service, which was confirmed by the NCDRC in appeal by the treating doctor. Deceased was father of a doctor who fought his own case on behalf of his mother, complainant in this case. This case will create awareness among doctors for taking informed consent in such case implied oral consent and help in preventing future litigations of such nature.